2006
DOI: 10.1021/jp055886d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Single-Molecule Conformational Distributions:  A Case Study with Poly-(l-proline)

Abstract: Precise measurement of the potential of mean force is necessary for a fundamental understanding of the dynamics and chemical reactivity of a biological macromolecule. The unique advantage provided by the recently developed constant-information approach to analyzing time-dependent single-molecule fluorescence measurements was used with maximum entropy deconvolution to create a procedure for the accurate determination of molecular conformational distributions, and analytical expressions for the errors in these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
187
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(193 citation statements)
references
References 71 publications
6
187
0
Order By: Relevance
“…Fig. 2f also shows that ligands cause AK's conformational distribution to become more compact when compared with that observed in the substrate-free case, results made possible using our methodology (32). This narrowing of the distribution can be understood in terms of AK's interaction with ligands, which restricts the range of motion that AK can otherwise experience.…”
Section: Effects Of Ligand Binding On the Conformation Distributionmentioning
confidence: 66%
See 1 more Smart Citation
“…Fig. 2f also shows that ligands cause AK's conformational distribution to become more compact when compared with that observed in the substrate-free case, results made possible using our methodology (32). This narrowing of the distribution can be understood in terms of AK's interaction with ligands, which restricts the range of motion that AK can otherwise experience.…”
Section: Effects Of Ligand Binding On the Conformation Distributionmentioning
confidence: 66%
“…This distribution could be equally well fit to a number of different models if one assumes the number of states present (e.g., one, two, or three) and their shapes (e.g., Gaussian or log-normal). To avoid subjective bias in interpreting the distribution, we applied our deconvolution technique to remove the broadening due to photon-counting noise (32). Based on the maximum entropy method, this procedure recovers the entire distribution of conformational states without a preassumed model regarding the number of states or the shape of the distribution.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying best-fit distance distributions can be δ functions 33 or narrow peaks (Figure 10), but could very possibly turn out to be wider in other experimental cases. Equipped with the tools presented in this work, researchers should now be able to make the two analytical steps evoked in the Introduction and extract meaningful information on distance distributions and energy landscapes.…”
Section: Extension To More Complex Systemsmentioning
confidence: 99%
“…I D is the donor excitation intensity, is the absorption cross section of the acceptor at the donor excitation wavelength. We can rewrite (32) Finally, following ref 14 (33) where is the absorption cross section of the donor at the donor excitation wavelength.…”
Section: Appendix C: Theoretical Expression Of ε In the Absence Of Bamentioning
confidence: 99%
“…37 Recently, it was shown that the existence of dynamic disorder of single enzymatic turnover reactions depends on how one assigns the ON/OFF levels and the most widely used binning and thresholding approach may yield a misleading interpretation. 38 Because some subsequences involving one step transitions in the ON/OFF time series were removed from the analyses, 16 it is desired to confirm how such removals would affect in the analyses based on change point detection method.…”
Section: Discussionmentioning
confidence: 99%